2011
DOI: 10.1111/j.1095-8312.2011.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeography reveals an antitropical distribution and local diversification of Solenogyne (Asteraceae) in the Ryukyu Archipelago of Japan and Australia

Abstract: An antitropical distribution represents an intriguing disjunction, in which a given species or sister lineages occupy regions north and south of the tropics but are absent from the intervening areas. Solenogyne mikadoi endemic to the Ryukyu Archipelago is regarded as an Australian element. Testing the phylogenetic relationship with Australian congeners and discussing the onset timing and causes of the disjunction would potentially enhance the understanding of antitropical distribution. A nuclear ribosomal DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 93 publications
1
18
0
Order By: Relevance
“…Anti-tropical relationships (where the same or sister taxa are absent from tropical regions, but are found to the north and south) are less common, but some examples occur between temperate Australia and mainland Asia-Japan. Among these taxa, older dispersal events are inferred in Sapindaceae (30-60 mya; Buerki et al 2011) and Apiaceae (46-71 mya; Calviño et al 2016); more recent dispersal events are inferred in Cucumis Linnaeus (1753bLinnaeus ( : 1011 in Cucurbitaceae (2-10 mya; Sebastian et al 2010), Solenogyne Cassini in Cuvier (1828: 174) in Asteraceae (0.9-4 mya; Nakamura et al 2012) and within Australian Poa sect. Brizoides Pilger ex Potztal (1969: 472) (1.4-6 mya; Birch et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-tropical relationships (where the same or sister taxa are absent from tropical regions, but are found to the north and south) are less common, but some examples occur between temperate Australia and mainland Asia-Japan. Among these taxa, older dispersal events are inferred in Sapindaceae (30-60 mya; Buerki et al 2011) and Apiaceae (46-71 mya; Calviño et al 2016); more recent dispersal events are inferred in Cucumis Linnaeus (1753bLinnaeus ( : 1011 in Cucurbitaceae (2-10 mya; Sebastian et al 2010), Solenogyne Cassini in Cuvier (1828: 174) in Asteraceae (0.9-4 mya; Nakamura et al 2012) and within Australian Poa sect. Brizoides Pilger ex Potztal (1969: 472) (1.4-6 mya; Birch et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…macroclinidioides , which coexist on Okinawa, had no fixed nucleotide differences, and they were not clustered separately. A previous study demonstrated the origin of the flood-resistant riparian species Solenogyne mikadoi , an endemic species in the Ryukyu Islands (Nakamura et al [31]). It showed that the divergence between Solenogyne mikadoi and the other Solenogyne species with disjunct distributions in southeastern Australia dated back several million years.…”
Section: Discussionmentioning
confidence: 99%
“…Several disjunct distributions in seed plants have been confirmed by molecular evidence, such as between North and South America (e.g., Spalik et al 2010;Popp et al 2011), between East Asia and North America (e.g., Huang et al, 2013), between Japan and Australia (e.g., Nakamura et al 2012;Kokubugata et al 2012), and between the Japanese Mainland and Taiwan (e.g., Mitsui et al 2008).…”
Section: Introductionmentioning
confidence: 90%